Upaya Meningkatkan Kemampuan Mengenal Lambang Bilangan Melalui Bermain Puzzle pada Anak Usia 4-5 Tahun di TK Tunas Inti Indragiri Hulu - Hariyanti Hariyanti; Helen F Sinambela; Widaningsih Widaningsih; Nuryanah Nuryanah (Jurnal Pendidikan Tuntas, 2023)
Mathematical knowledge in early childhood, especially knowledge about understanding the concept of numbers, is very important and must be prepared as well as possible so that it will contribute to students' success in everyday life and success in the future. The aim of this research is to improve the ability to recognize number symbols through playing puzzles in children aged 4-5 years at Tunas Inti Indragiri Hulu Kindergarten. This type of research is Classroom Action Research (PTK) using the Kemmis and Mc model research design. Taggart. The research subjects were all group A children at Tunas Inti Indragiri Hulu Kindergarten. The number of children is 20, consisting of 10 boys and 10 girls. This classroom action research was carried out through two cycles. Each cycle consists of two meetings. The results of the research were that in the pre-cycle the average child's score was only 41.50% in the Not Yet Developed category, but after playing the puzzle game in Cycle 1 the child's average score increased to 67.65%, but this score did not meet the indicators of success. So the researchers continued improvements in cycle 2 with an average score of 84.67%. The improvement in the ability to recognize number symbols for children aged 4-5 years at Tunas Inti Indragiri Hulu Kindergarten in cycle 2 has met the success criteria so that it does not require reflective action and the research is considered complete. Keywords: Symbols for Numbers, Games, Puzzles